2019
DOI: 10.1093/omcr/omz038
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-hypotension with acute pulmonary oedema due to simultaneous bilateral subclavian artery stenosis in a patient with coronary artery bypass graft surgery using bilateral internal mammary arteries: a case report

Abstract: A 75-year-old woman, with a history of bilateral internal mammary artery–coronary artery bypass graft surgery, developed hypotension and pulmonary oedema posing as cardiogenic shock. Severe bilateral subclavian artery stenosis emerged to be the cause of ischaemic myocardial dysfunction and heart failure. An emergency endovascular treatment was successfully performed. The presence of simultaneous bilateral subclavian artery narrowing as the pathophysiologic mechanism of myocardial ischaemia makes this case rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…SAS is a form of upper extremity PAD which should be suspected when exam findings reveal a BP differential of 15 mmHg or more in the arms [ 5 , 6 ] , especially in patients with known lower PAD. Atherosclerosis has been identified as the most frequent cause, followed by fibromuscular dysplasia, compression syndrome and Takayasu arteritis [ 2 , 7 ] . The pathophysiology of atherosclerotic SAS has been described as a process of cell adhesion: inflammatory cells attaching to the arterial wall, with arterial wall remodelling and lipid accumulation resulting in calcification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SAS is a form of upper extremity PAD which should be suspected when exam findings reveal a BP differential of 15 mmHg or more in the arms [ 5 , 6 ] , especially in patients with known lower PAD. Atherosclerosis has been identified as the most frequent cause, followed by fibromuscular dysplasia, compression syndrome and Takayasu arteritis [ 2 , 7 ] . The pathophysiology of atherosclerotic SAS has been described as a process of cell adhesion: inflammatory cells attaching to the arterial wall, with arterial wall remodelling and lipid accumulation resulting in calcification.…”
Section: Discussionmentioning
confidence: 99%
“…When bilateral subclavian arteries are stenosed, the difference in upper extremity BPs may be concealed, making comparison to lower extremity BP measurements, as seen in tests such as ABIs, critically important. Though the ABI test is not validated in longitudinal studies, it has been utilized to diagnose bilateral SAS in previously reported cases [ 2 ] . If there is suspicion for SAS but comparison of bilateral upper extremity BP measurements is unrevealing, an ABI showing higher-than-normal values (ABI >1.3) can prompt the provider to investigate for bilateral SAS, and consider more conclusive testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation